The detectation of plagiarism evidences in academic papers - A software to support and automate the processRoseclea Duarte Medina1, Catiane Priscila Barbosa Arenhardt21,2 Universidade Federal de Santa Maria - UFSM - Centro de Tecnologia – Programa de Pós-graduação em Informática - Mestrado em Compu-tação - roseclea.medina@gmail.comResumoO fácil acesso as informações devido a difusão da internet, possibilita o enriquecimento intelectual, mas por vezes acaba por ser um meio de usufruir do conhecimento de outrem sem mencionar seus créditos/direitos autorais, o que por fim acaba na configuração do plágio. O plágio no meio acadêmico é uma tarefa difícil de ser controlada, devido o grande número de trabalhos que são feitos por uma vasta quantidade de alunos e também pelo excesso de tarefas dos professores e pelo pouco tempo que conseguem dedicar para o controle da qualidade e autenticidade dos trabalhos. Com isso, é importante contar com softwares que auxiliem no processo de verificação de indícios de plágio, desta maneira o presente trabalho vislumbra aprimorar o método DIP – Detector de Indícios de Plágio para auxiliar o docente na verificação da autenticidade dos trabalhos.Palavras Chave: softwares, indícios de plágio, AbstractThe easy access to information due to the Internet’s diffusion enables the intellectual enrichment. However, oftentimes, it ends up being a way to use someone else’s knowledge without mentioning them in the credits or their authorial rights. Such process is called plagiarism. Plagiarism in the academic world is a difficult task to be controlled because of the great amount of papers, which are done by a vast quantity of students, and the excess of professors’ tasks e their limited time to work on the control of quality and authenticity of the papers. Thus, it is important to rely on software that supports the process of fiding plagiarism evidences. That being said, the present papers aims to improve the DIP method – Plagiarism Evidences Detector – to support the professor in the verification of the authenticity of papersKeyworks: softwares, Plagiarism Evidences, - Medina, Roseclea Duarte; Arenhardt, Catiane Priscila Barbosa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
The easy access to information due to the Internet’s diffusion enables the intellectual enrichment. However, oftentimes, it ends up being a way to use someone else’s knowledge without mentioning them in the credits or their authorial rights. Such process is called plagiarism. Plagiarism in the academic world is a difficult task to be controlled because of the great amount of papers, which are done by a vast quantity of students, and the excess of professors’ tasks e their limited time to work on the control of quality and authenticity of the papers. Thus, it is important to rely on software that supports the process of fiding plagiarism evidences. That being said, the present papers aims to improve the DIP method – Plagiarism Evidences Detector – to support the professor in the verification of the authenticity of papers.